INCREASE IN SELF-CONFIDENCE AND CRITICAL THINKING SKILLS USING THE TALKING STICK METHOD - Masfufah, Laeli; Gunawan, Gunawan; Kusuma, Jaka Wijaya; Setyaningsih, Eka; Ristianto, Mega (Yayasan Education and Social Center, 2024)
This study aims to determine the improvement of self-confidence and critical thinking skills of grade II students at SD Negeri 1 Kedungbanteng through the application of the talking stick learning method in Civic Education lessons. This type of research is classroom action research which is carried out in 2 cycles. The research instruments used were in the form of observation sheets for confident attitudes and tests for critical thinking skills. The results of the study showed that the self-confidence attitude of grade II students increased through learning using the talking stick. The percentage of students with a minimum self-confidence attitude was in the high category in the first cycle of 70.4%, increasing in the second cycle to 77.8%. Students' critical thinking skills have improved each cycle. The improvement of students' critical thinking skills from the average pre-action score of 64.25 to 69.63 in the first cycle and increased to 78.25 in the second cycle. Students who achieved the completeness criteria increased from 43.75% in the pre-action to 62.5% in the first cycle and increased to 87.5% in the second cycle. The results of the observation also showed an increase in student activities from cycle I to cycle II, namely as many as 25% of students increased their activities, including activeness in learning, students were more free to search and collect the desired information, and students also had more opportunities to learn with friends